Photosynthesis, respiration and stomatal resistance in Phaseolus vulgaris as a function of water and nitrogen levels - Costa, Roberto C. Lobo da; Lopes, Nei F.; Oliva, Marco A.; Barros, Nairan F. de (Pesquisa Agropecuaria Brasileira, 2014)
Net photosynthesis, respiration and stomatal resistance were studied in Phaseolus vulgaris L. cv. Negrito 897, under three nitrogen levels (50, 125 and 200 ppm) and two water regimes, field capacity (≈-0.03 MPa) and cyclic water deficit (≈-0.03 to -1.0 MPa), in the greenhouse. The determinations were made on the first, third and fifth leaves. Stomatal resistance and dark respiration increased with water deficit while photosynthesis decreased. Plants grown at field capacity showed an increase in the net photosynthetic rate and a decrease in stomatal resistance with increasing nitrogen levels. The fifth leaf exhibited an increase in stomatal resistance with enhanced nitrogen levels. Dark respiration rates did not show a clear relation with nitrogen levels and stomatal resistance in all leaves studied. In stressed plants, there was no relation between photosynthetic rates and nitrogen levels in the three leaf ages. The physiological parameters studied were more affected by water regime than by nitrogen level. However, nitrogen promoted a marked plant adaptation to water stress by reducing its effect.